THE EFFECTIVENESS OF THINK-TALK-WRITE (TTW) STRATEGY ON STUDENTS’ WRITING SKILL OF THE TENTH GRADE STUDENTS AT SMKN 1 SUKASADA IN THE ACADEMIC YEAR 2019/2020 - Asvini, K. D.; Suputra, P. E. D.; Hadisaputra, I. N. P. (Jurnal Pendidikan Bahasa Inggris undiksha, 2020)
This research aimed at investigating whether or not the use of Think Talk Write (TTW) strategy has an effect on the writing skill of tenth grade students’ at SMKN 1 Sukasada in writing narrative text. This experimental study was carried out using Non-Equivalent Control Group Design. There were two classes chosen as sample, experimental and control group. The obtained data were analyzed descriptively and inferentially. The results of data analysis showed that mean score of experimental group (74.82) was higher than control group (71.22). Moreover, result of independent t-test revealed that there was a significant difference on students’ writing skill (Sig.(2-tailed) = 0.008, p < 0.05). These results indicated that Think Talk Write (TTW) strategy gave significant effect on writing skill of tenth grade students at SMKN 1 Sukasada. As conclusion, alternative hypothesis is accepted in which the students from experimental group achieve better than those students from control group.Keywords: Narrative Text, Think Talk Write (TTW) Strategy, Writing Skill